2001
DOI: 10.1080/13504850010018743
|View full text |Cite
|
Sign up to set email alerts
|

Wagner's law revisited: cointegration and exogeneity tests for the USA

Abstract: This paper re-examines Wagner's hypothesis of an expanding government sector with progress of the economy using advanced econometric techniques such as cointegration and exogeneity tests not used in previous empirical studies. This study also uses much longer time series data for the USA than previously utilized. The empirical results based on cointegration and exogeneity tests provide strong support for the hypothesis for the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 16 publications
2
44
0
4
Order By: Relevance
“…{Insert Table 4 about here} Our implied income elasticity estimates are comparable to Ahsan et al (1996) for Canada, Islam (2001) for USA, Kolluri et al (2000) for the G7 countries and Arpaia and…”
Section: Cointegrationmentioning
confidence: 68%
See 1 more Smart Citation
“…{Insert Table 4 about here} Our implied income elasticity estimates are comparable to Ahsan et al (1996) for Canada, Islam (2001) for USA, Kolluri et al (2000) for the G7 countries and Arpaia and…”
Section: Cointegrationmentioning
confidence: 68%
“…Biswal et al (1999) also find bidirectional causality for Canada. Islam (2001) found strong support for Wagner's Law (eq. 1) for the USA with income elasticity estimates of around 0.4 and a Granger-causality from GDP to government expenditure.…”
Section: Literature To Datementioning
confidence: 93%
“…However, according to a review by Peacock and Scott (2000), previous empirical studies dealing with Wagner's law use different measures for government size and economic development. One of the most commonly used representations is based on Musgrave (1969), who interprets the law as implying that the share of total government expenditure in GDP increases with per capita income (e.g., Lall, 1969;Mann, 1980;Ram, 1987;Islam, 2001;Chang, 2002;Chang et al, 2004;Shelton, 2007;Durevall and Henrekson, 2011). In regression formula, the specification can be represented as…”
Section: Government Size Economic Development and Datamentioning
confidence: 99%
“…The empirical evidence from this literature is however mixed and controversial across countries, data, model specifications and econometric techniques. While some studies (Ram, 1987;Ahsan et al, 1996;Cotsomitis et al, 1996;Thornton, 1999;Islam, 2001;Al-Faris, 2002;Chang, 2002;Aregbeyen, 2006;Srinivasan, 2013;Bayrak and Esen, 2014) found support for Wagner's Law, other studies (Ansari et al, 1997;Biswal et al, 1999;Ghali, 1999;Burney, 2002;Huang, 2006) reported results contradicting Wagner's law. Some other studies (Singh & Sahni, 1984;Ahsan et al, 1992;Afxentiou & Serletis, 1996;Sinha, 1998;Bagdigen & Cetintas, 2004;Dogan & Tang, 2006) showed no evidence for both propositions.…”
Section: Introductionmentioning
confidence: 99%